Proyecto de factibilidad para la implementación de una empresa productora y comercializadora de enlatado de tilapia en el cantón Lago Agrio, provincia de Sucumbíos, para el año 2015 - Ramírez Arteaga, Irma Elizabeth (2015)
The overall objective for this project is to determine the commercial viability of implementing a producer and marketer of canned tilapia in the canton Lago Agrio, using methods and techniques that facilitate the development of research, which helped to achieve results expected and the feasibility of it, for which the demand, supply, technical probability, organizational structure, financial structure and social and environmental assessment of the producer and marketer of canned tilapia determined. This project is feasible to run because as shown by the studies; the market study was conducted based on a survey of the economically active population of Lago Agrio canton 2015 (44,348); then it proceeded to determine the potential demand, real, effective and supply; obtaining an unmet demand of 540,451 cans of canned 180g tilapia, which will cover the expectations of demand. As for the technical study the first year the installed capacity was determined 506,880, 481,536 capacity utilization and optimal location of the company; Lago Agrio Canton via quito km 6 left margin in the arazá neighborhood, as well as the production process of canned tilapia and its respective process diagram to determine how many units of canned tilapia can be produced in the new company. Later the organizational study of the company was conducted, which is constituted as a limited liability company, in addition to the organizational structure of the same is determined, ie the requirements for legalization, permits, records and manual functions for employees. Fixed investments for the project are quantified in dollars USD $ 208,882.05 United States of America, working capital USD $ 41,222.32 dollars of the United States of America, deferred investment USD to $ 3762.51 US from America. Then the total investment of the project is USD $ 253,886.88 dollars of the United States of America for the project financing of USD $ 80,000.00 dollars of the United States of America will be obtained at a rate of interest 11.20%, awarded by the National Development Bank. The financial assessment for the project is viable with the following financial indicators; VAN of USD $ 3,793.82 dollars the United States of America; TIR of 12%; Benefit Cost Ratio $ USD $ 1.22 United States of America, Capital Recovery Period three years, three months, six days and sensitivity analysis 0.99 with increasing costs and 10.01% decrease in revenues 8.16%. Environmental impacts and socioeconomic have an average negative impact on physical factors such as water, vibration and air; in the socio-economic factors is positive means, it does not affect society but rather favors it, generating sources of employment that contribute to the development and good living of society and specially to generate profit and gain the creator of the project. Finally, the conclusions that were reached by the study are presented. The general objective and specific objectives of the thesis is answered; and recommendations set out to increase the economic value of the company.